Health underachievement and overachievement in English local authorities - Doran, Tim (BMJ Group, 2006)
OBJECTIVE: To identify English local authorities that “overachieve” and “underachieve” in health terms, given their level of deprivation, sociodemographic context, and region. DESIGN: Cross sectional study using data from the 1991 UK census and mortality data from 2000–2. SETTING: England. PARTICIPANTS: 354 local authorities (total population 49 558 000). MAIN OUTCOME MEASURES: Life expectancy. Residual life expectancy after regression analysis. RESULTS: In general, the more materially deprived the population of a local authority was in 1991, the lower its life expectancy a decade later, with men being more sensitive to the effects of deprivation than women. Many local authorities, however, did not follow this general trend, and these shared common characteristics. Mining, Manufacturing and Industry, and Urban Fringe authorities collectively had lower life expectancies than predicted by their level of deprivation, as did authorities located in the north west. Outer London and Education Centres and Inner London authorities had much higher life expectancies than predicted, as did authorities located in the east, south east, and south west. Given their level of deprivation, sociodemographic context, and region, 11 local authorities significantly overachieved for male life expectancy and 10 underachieved, while 12 overachieved for female life expectancy and three underachieved. CONCLUSIONS: Life expectancy in English local authorities is strongly associated not only with material deprivation, but with the local sociodemographic context and the region where the authority is located. Some authorities defy their contexts, however, and overachieve in health terms, while others, including some in affluent areas, underachieve.